Professional preferences and academic performance in mathematics students of the National University of San Augustin - Arequipa (Perú) - Checya Aquise, Rode (2018)
The present study analyzes the relationship between professional preferences and the academic performance of a group of students of Mathematics of the National University of San Agustín - Arequipa. To do this, a non-probabilistic sample of 68 students (66.17% men and 33.83% women) was taken, the Professional Preferences Profile Test was applied, and their average grade in mathematics was recorded. The results show that there is no connection between professional preferences and the academic performance of students. However, there are significant differences corresponding to sex and semester of study. So that men are more realistic and women more artistic, and the seventh-semestrer students have higher scores in research and third-semester students have higher scores in entrepreneurship.